1973
DOI: 10.21273/hortsci.8.3.220
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Cucumber to Trellis vs. Ground Culture1

Abstract: Marketable yield increase of 100% resulted from trellising fresh market cucumbers (Cucumis sativus L.) over a 3-year period. Fruit were a more uniform, dark green color and graded more Fancy and fewer Culls. Fungicidal control of scab (causal agents Cladosporium cucumerinum Ell. & Arth.) was improved by trellising and losses to soil rot (causal agentsRhizoctonia solani Kuhn and Pythium spp.) were eliminated. Suggested reasons for improved yield and quality from trellising include less damage to vines, grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similar advantages in yield and appearance of trellis-grown cucumbers as compared with groundgrown cucumbers have long been appreciated (Konsler and Strider, 1973;Hanna et al, 1987;Russo et al, 1991;Nair et al, 2013). fruit quality by increasing the exposure of the plant foliage to sunlight, thereby increasing photosynthesis, with increased ventilation and reduced exposure of the fruits to soil-borne pathogens and damage-causing ground-dwelling arthropods (Konsler and Strider, 1973;Pradhan et al, 2021;Buck-Sorlin et al, 2023). Trellising is today a widely commercially applied method for growing fresh-market cucumbers (Parker et al, 2019;Rutgers New Jersey Agricultural Experiment Station, 2022).…”
Section: Yieldmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar advantages in yield and appearance of trellis-grown cucumbers as compared with groundgrown cucumbers have long been appreciated (Konsler and Strider, 1973;Hanna et al, 1987;Russo et al, 1991;Nair et al, 2013). fruit quality by increasing the exposure of the plant foliage to sunlight, thereby increasing photosynthesis, with increased ventilation and reduced exposure of the fruits to soil-borne pathogens and damage-causing ground-dwelling arthropods (Konsler and Strider, 1973;Pradhan et al, 2021;Buck-Sorlin et al, 2023). Trellising is today a widely commercially applied method for growing fresh-market cucumbers (Parker et al, 2019;Rutgers New Jersey Agricultural Experiment Station, 2022).…”
Section: Yieldmentioning
confidence: 88%
“…The fruits of the trellised plants were uniformly black-green over their entire surface, without a lightcolored ground spot (Figure 2). Similar advantages in yield and appearance of trellis-grown cucumbers as compared with groundgrown cucumbers have long been appreciated (Konsler and Strider, 1973;Hanna et al, 1987;Russo et al, 1991;Nair et al, 2013). fruit quality by increasing the exposure of the plant foliage to sunlight, thereby increasing photosynthesis, with increased ventilation and reduced exposure of the fruits to soil-borne pathogens and damage-causing ground-dwelling arthropods (Konsler and Strider, 1973;Pradhan et al, 2021;Buck-Sorlin et al, 2023).…”
Section: Yieldmentioning
confidence: 89%
“…It has been reported that vertical training of cucumber can improve fruit yield and quality (Baker, 1977and Hanna and Adams, 1987& 1993. Moreover, Konsler and Strider (1973) found that the trellising enhanced the disease control of foliage and fruits, and simplified harvesting as fewer fruits were overlooked into oversize or cull fruits. Consequently, trellised plants may remain more healthy and productive for a longer period.…”
Section: Introductionmentioning
confidence: 99%